METAPHOR AS A TOOL FOR REPRESENTING KNOWLEDGE STRUCTURES - Tumparova Guzal Radikovna (XALQARO ILMIY-AMALIY ANJUMAN “GLOBAL LINGVISTIKA: YANGI YONDASHUVLAR VA TADQIQOTLAR”, 2025)
The article is dedicated to examining the role of metaphor in the formation and representation of knowledge structures in light of the linguocognitive approach. It is argued that metaphor is not only a stylistic device but also an important tool for a deeper perception of literary text. Based on the analysis of examples from English-language literary texts, it is concluded that metaphors activate universal and culturally specific representations of reality through the prism of images and concepts characteristic of different cultures; contribute to the creation of associative-image models that reflect human feelings and emotional states, and the interpretation of complex abstractions.